PELAKSANAAN PEMBINAAN NARAPIDANA DI RUMAH TAHANAN NEGARA KLAS II B SIAK, KABUPATEN SIAK - ", Nuraisah; Rosaliza, Mita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted in Siak Subdistrict, Siak District. The purpose of this study is to determine the implementation of guidance of prisoners in Rutan Siak. The focus of this research is to know the implementation of guidance of prisoners and the inhibiting factors in the implementation of guidance of prisoners in the Second Class State Detention Unit B Siak, so that prisoners can live as normal human beings or re-socialization. The subject of this research is the detainee service officer as responsible for the implementation of guidance of the prisoner, that is 5 people. The author uses qualitative descriptive method. Instrument data is observation, interview and documentation. The results of this study indicate that the implementation of coaching goes well, despite the lack of awareness of self-inmates to make changes and lack of infrastructure in the implementation of coaching.Keywords: Re-Socialization, Coaching, Prisoners, Siak.